Gambaran Pemenuhan Kebutuhan Spiritual Pada Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisa di Rumah Sakit Bhayangkara Kota Jambi - Maulani Maulani; Nofrida Saswati; Dewi Oktavia (STIKes Karsa Husada Garut, 2021)
Chronic renal failure (CRF) is a terminal disease that affects the patient's quality of life. GGK creates biological, psychological, social and spiritual imbalances. Spiritual distress can be in the form of a relationship with god and things like life satisfaction, direction in life, and purpose in life. If spiritual needs are bad it can lead to serious psychological disorders such as suicide. This study aims to describe the spiritual needs of patients with chronic renal failure undergoing hemodialysis. This research is a quantitative research with descriptive research methods. The population in this study were all CRF patients who underwent hemodialysis in the Hemodialysis Room at Bhayangkara Hospital, Jambi City in August 2020, totaling 35 patients and the sampling was carried out using total sampling technique, amounting to 35 patients. The data was collected using a questionnaire sheet and the results of the research were analyzed univariately. The results showed that 31 (88.6%) respondents had spiritual needs fulfilling in the form of religious well-being (RWB) in the medium category and there were 19 (54.3%) respondents who fulfilled their spiritual needs in the form of existential well-being (EWB). low category in patients with chronic renal failure undergoing hemodialysis. It is hoped that the hospital, especially nurses who work in the hemodialysis room, should make a program that supports group spirituality activities according to the beliefs of each client (support group). Nurses are expected to be able to provide nursing care with a spiritual approach (spiritual care) and holistically